DAMPAK PERILAKU BULLYING TERHADAP PERCAYA DIRI SISWA KELAS IV SD NEGERI 1 KAREKAN PAGENTAN BANJARNEGARA - Hesti Ariska Dewi; Andriani, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of bullying behavior on the self-confidence of fourth-grade students at SD Negeri 1 Karekan, Pagentan, Banjarnegara, and to identify the contributing factors behind bullying incidents. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings revealed that bullying occurred in verbal, physical, and social forms. The impacts included decreased self-confidence, fear of speaking in front of the class, social withdrawal, emotional distress, and reduced learning motivation. The primary contributing factors were lack of parental supervision, emotional distance due to parents working out of town, and exposure to inappropriate social media content. Perpetrators were generally dominant students lacking empathy. This study highlights the urgent need for collaboration between schools and parents to prevent bullying and foster character development and social awareness among students.